Unravelling the Tangle of Bureaucracy at Russian Universities: Administrative Profiles - T. A. Akuneeva; D. P. Platonova (Высшее образование в России)
Drawing on the analysis of staff restructuring in universities around the world, the article stresses the growing share of non-academic staff, in particular highly qualified middle and senior administrative staff.   The purpose of the article is to analyze how a combination of different categories of administrative staff is represented in universities according to their functions.   Based on the cluster analysis of the Monitoring of education markets and organizations (N = 92), three groups of universities were identified according to administrative profiles: enterprising, educational and infrastructural. The first cluster is characterized by a high proportion of administrative staff engaged in general management, research, financial issues and information and communication technologies. The second cluster has a high proportion of staff engaged in providing educational activities. The third cluster is characterized by a high proportion of personnel engaged in the maintenance and operation of infrastructure and buildings. Universities with an infrastructural administrative profile are characterized by the presence of a larger area of educational and laboratory facilities per student, however, universities in the sample do not differ in terms of scientific, educational and financial activities.